Internal standard for amorphous pharmaceuticals products quantification and an application of Parametric Rietveld refinement using time, temperature and relative humidity as 'non-crystallographic' parameters - Nunes, Rafael Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Os estudos recentes sobre fármacos sólidos por difração de raios X por pó (DRXP) no Brasil vem demonstrando o quão importante pode ser esta técnica, principalmente aliada ao método de Rietveld, para a compreensão estrutural destes materiais. Materiais amorfos tem uma energia interna maior que a energia interna de materiais cristalinos. Isto pode influenciar diretamente o efeito terapêutico de um medicamento, e isto faz da quantificação de amorfo um estudo importante. Como a utilização de um padrão com reconhecimento internacional, como o padrão NIST SRM-676a (Al2O3), pode ser economicamente inviável, foi feito uma caracterização sistemática, principalmente por DRXP, de um material barato e com coeficiente de absorção linear dos raios X da ordem destes produtos orgânicos, a ser usado como padrão interno em análises quantitativas de fases. Os bons resultados obtidos com LiF, como padrão interno, na quantificação de amorfo à temperatura ambiente, mostrou seu potencial para uma aplicação em larga escala (quando comparados aos obtidos pelo padrão NIST SRM-676a, considerando o efeito de microabsorção). Outro importante foco deste trabalho foi a DRXP in situ aplicada aos produtos farmacêuticos e teve como destaques: uma câmara chamada TUCANO, para aplicar umidade relativa em experimentos de difração de raios x por pó in situ, desenvolvida em colaboração com o Laboratório Nacional de Luz Síncrotron (LNLS); a aplicação, pioneira no Brasil, do refinamento de Rietveld Paramétrico e o primeiro uso da umidade relativa como parâmetro “não cristalográfico” neste refinamento; e aplicação dos padrões internos (SRM-676a e LiF) em experimentos em função do tempo (com temperatura constante), temperatura e umidade relativa (UR). Norfloxacino (NF, C16H18FN3O3), possui uma alta suscetibilidade estrutural à umidade relativa e depois da cristalização da forma...

Recent studies on solid polycrystalline drugs by x-ray powder diffraction (XRPD) in Brazil, has demonstrated how important this technique can be, especially joined to Rietveld method, for structural understanding of these materials. Amorphous material has a higher internal energy than crystalline materials, what alters their therapeutic effects and it makes of amorphous quantification an important study. As an internal standard with international recognition for this purpose, such as NIST SRM-676a (Al2O3), can be economically unviable, a systematic characterization, mainly by XRPD, of a cheap material with liner coefficient absorption of same order of this organic products, to use as internal standard for quantitative phase analysis was made. Good results obtained with LiF, as internal standard, for amorphous pharmaceutical quantification at room temperature, shows its potential for a large-scale application (when compared to results obtained using NIST standard SRM-676a, considering microabsorption effect). Other important focus of this work was in situ XRPD applied to pharmaceutical products and had as highlights: a chamber called TUCANO, to use relative humidity in experiments of in situ XRPD, developed with cooperation of Brazilian Synchrotron Light Source (LNLS); the Parametric Rietveld refinement, pioneered applied in Brazil; the first use of relative humidity as ‘non-crystallographic’ parameter in this refinement; and the application of internal standards (SRM-676a and LiF) during experiments in function of time (at constant temperature), temperature and relative humidity (RH). Norfloxacin (NF, C16H18FN3O3), has a high structural susceptibility to RH and after crystallization of Norfloxacin sesquihydrate form (the only with known crystal structure) starts, at high RH, the behaviour of its cell parameters were parameterized to obtain a smoothly behaviour between all powder patterns...
Keywords: Físico-química; Norfloxacino; Fármacos; Drugs